Contesting Hadith Authority: The Socio-Religious Construction of Tabarruk in Muhammad Alawi al-Māliki’s Thought - Rohmansyah Rohmansyah (Diroyah : Jurnal Studi Ilmu Hadis, 2026)
A controversial issue among scholars is tabarruk. Tabarruk is interpreted as taking blessings from people who are still alive and have died. For example, taking blessings from the Prophet, scholars and people who are considered noble. This research aims to analyze Muhammad Alawi al-Maliki's understanding of tabarruk. The research method used is a qualitative method based on library research data. The findings of this study explicitly show that the understanding of the hadith of Muhammad Alawi al-Maliki is very elastic. He used the hadiths and atsar of the companions as an argument for the evidence about tabarruk. Not only that, the hadiths of the Prophet that are used as evidence are not only valid but also hasan. Interestingly, he reads and understands the hadith not only textual but contextual. This is understood from his understanding of tabarruk. According to him, Tabarruk is not only done to the Prophet, the companions but also to pious people including wali and ulama. This aspect of understanding is influenced by his teachers and the conditions of social interaction, where he was born and lived, so that this ability of tabarruk is a rebuttal to those who consider him bid’ah.